2011
DOI: 10.4317/medoral.17098
|View full text |Cite
|
Sign up to set email alerts
|

Tongue lesions in a Jordanian population. Prevalence, symptoms, subject s knowledge and treatment provided

Abstract: Tongue lesions constitute a considerable proportion of oral mucosal lesions, and are health concern to both oral health care providers and public. Objectives: The aim of this study was to determine the prevalence of tongue lesions and conditions among a group of Jordanian population attending dental clinics, in addition to assessment of their symptoms, knowledge, and treatment provided for their tongue lesions. Study design: A total of 2000 dental out-patients were screened for tongue lesions. Results: Fissure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
48
5
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 14 publications
11
48
5
6
Order By: Relevance
“…As performed in previous investigations, patient age was subdivided into 10-year intervals for analysis purposes. [8][9][10] Locations of the lesions were arbitrarily classified into dorsal, ventral and lateral surfaces according to the information provided in the patients' records and anterior/posterior localization was also specified where accessible. In order to facilitate further evaluation of lesion types, all defects were categorized into eight groups including developmental, immune-mediated, reactive, benign, premalignant, malignant, retention/inflammatory salivary gland-related and miscellaneous.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As performed in previous investigations, patient age was subdivided into 10-year intervals for analysis purposes. [8][9][10] Locations of the lesions were arbitrarily classified into dorsal, ventral and lateral surfaces according to the information provided in the patients' records and anterior/posterior localization was also specified where accessible. In order to facilitate further evaluation of lesion types, all defects were categorized into eight groups including developmental, immune-mediated, reactive, benign, premalignant, malignant, retention/inflammatory salivary gland-related and miscellaneous.…”
Section: Methodsmentioning
confidence: 99%
“…8,9 There are several reports from around the world that have studied the clinical prevalence of tongue pathoses, [8][9][10][11][12][13][14][15][16][17] supplying valuable information that can not only be used as references for local practicing clinicians, but also assist in a better understanding of the variations between different countries and eventually offering more specific insight into the possible influencing factors responsible for some lesions. Thus presenting more recent detailed data on the frequency and demographic characteristics of diseased conditions from different geographic regions seems imperative, especially considering the ongoing modifications in patient lifestyle and a general shift toward growing public awareness and sensibility to oral health leading to possible changes in disease pattern.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 On the other hand, another study also found that fissured tongue was the most common tongue lesion diagnosed in 11.5% of the subjects comprised of 2,000 dental out patients that have been screened for tongue lesions. 10 The older someone the more fissured tongue may be found that might be caused by reduction of elastic fibers in oral tissue. This lesion is benign and does not need special treatment, only required to increase tongue hygiene.…”
Section: Discussionmentioning
confidence: 99%
“…6 Literatürde ilginç olarak OML hakkın-daki çalışmaların önemli bir kısmının diş hekimliği bölümlerine başvuran hastalar arasında yürütül-düğü fark edilmektedir. 1,5,[7][8][9][10][11][12][13][14][15][16][17][18][19] Ayrıca Türk toplumunda OML üzerine yapılmış epidemiyolojik çalışma sayısının da oldukça yetersiz olduğu gö-rülmektedir. [19][20][21][22][23][24] Bu çalışmada herhangi bir deri hastalığı şikayeti nedeniyle dermatoloji polikliniğine başvuran hastalarda OML varlığı değerlendi-rilerek OML tipi, nedeni, sıklık ve dağılım özellikleri araştırılmıştır.…”
unclassified